Dipyridamole enhances ischaemia-induced arteriogenesis through an endocrine nitrite/nitric oxide-dependent pathway - Venkatesh, Prasanna K. (Oxford University Press, 2010)
AIMS: Anti-platelet agents, such as dipyridamole, have several clinical benefits for peripheral artery disease with the speculation of angiogenic potential that could preserve ischaemic tissue viability, yet the effect of dipyridamole on ischaemic arteriogenesis or angiogenesis is unknown. Here we test the hypothesis that dipyridamole therapy augments arteriolar vessel development and function during chronic ischaemia. METHODS AND RESULTS: Mice were treated with 200 mg/kg dipyridamole twice daily to achieve therapeutic plasma levels (0.8–1.2 µg/mL). Chronic hindlimb ischaemia was induced by permanent femoral artery ligation followed by measurement of tissue perfusion using laser Doppler blood flow along with quantification of vascular density, cell proliferation, and activation of nitric oxide (NO) metabolism. Dipyridamole treatment quickly restored ischaemic hindlimb blood flow, increased vascular density and cell proliferation, and enhanced collateral artery perfusion compared with control treatments. The beneficial effects of dipyridamole on blood flow and vascular density were dependent on NO production as dipyridamole did not augment ischaemic tissue reperfusion, vascular density, or endothelial cell proliferation in endothelial NO synthase (eNOS)-deficient mice. Blood and tissue nitrite levels were significantly higher in dipyridamole-treated mice compared with controls and eNOS(−/−) mice, verifying increased NO production that was regulated in a PKA-dependent manner. CONCLUSION: Dipyridamole augments nitrite/NO production, leading to enhanced arteriogenesis activity and blood perfusion in ischaemic limbs. Together, these data suggest that dipyridamole can augment ischaemic vessel function and restore blood flow, which may be beneficial in peripheral artery disease.